Three-dimensional modeling and porosity calculation of coal rock pore structure - Li, Qiong; Chen, Zheng; Yue, Lin; Zhang, Yu; He, Jian-Jun; Li, Yong (Applied geophysics, 2022)
Coal rock is a type of dual-porosity medium, which is composed of matrix pores and fracture-cutting matrix. They play different roles in the seepage and storage capacity of coal rock. Therefore, constructing the micropore structure of coal rock is very important in the exploration and development of coalbed methane. In this study, we use a coal rock digital core and three-dimensional modeling to study the pore structure of coal rock. First, the micropore structure of coal rock is quantitatively analyzed using a two-dimensional thin-section image, and the quantitative information of the pore and fracture (cleat) structure in the coal rock is extracted. The mean value and standard deviation of the face porosity and pore radius are obtained using statistical analysis. The number of pores is determined using dichotomy and spherical random-packing methods based on compression. By combining with the results of the petrophysical analysis, the single-porosity structure model of the coal rock is obtained using a nonequal-diameter sphere to represent the pores of the coal rock. Then, an ellipsoid with an aspect ratio that is very much lesser than one is used to represent the fracture (cleat) in the coal rock, and a dual-pore structure model of the coal rock is obtained. On this basis, the relationship between the different pore aspect ratios and porosity is explored, and a fitting relationship is obtained. The results show that a nonlinear relationship exists between them. The relationship model can provide a basis for the prediction of coal rock pore structure and the pore structure parameters and provide a reference for understanding the internal structure of coalbed methane reservoirs.